2017
DOI: 10.1002/etc.3732
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic toxicity of photo‐degraded insensitive munition 101 (IMX‐101) constituents

Abstract: Insensitive munitions are desirable alternatives to historically used formulations, such as 2,4,6-trinitrotoluene (TNT), because of their so-called insensitivity to unintended detonation. The insensitive munition IMX-101 is a mixture of 2,4-dinitroanisole (DNAN), 3-nitro-1,2,4-triazol-5-one (NTO), and nitroguanidine (NQ). Environmental releases of munitions may be from production wastewaters or training; these munitions may be exposed to ultraviolet (UV) light. Therefore, it is useful to understand the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 25 publications
(66 reference statements)
1
57
2
Order By: Relevance
“…Even though UV treatment clearly caused increased toxicity of MeNQ in fathead minnows (Table ), the magnitude of increased toxicity is lower than has been reported for UV‐degraded NQ in previous experiments (Gust et al ; Kennedy et al ; Moores et al ). Kennedy et al () reported a 73‐fold lower LC50 for UV‐treated NQ compared with NQ parent compound in C. dubia . Moores et al () demonstrated the greatest increase in toxicity yet observed for UV‐degraded NQ, where 90% UV degradation of NQ elicited a 1240‐fold increase in toxicity in Daphnia pulex .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Even though UV treatment clearly caused increased toxicity of MeNQ in fathead minnows (Table ), the magnitude of increased toxicity is lower than has been reported for UV‐degraded NQ in previous experiments (Gust et al ; Kennedy et al ; Moores et al ). Kennedy et al () reported a 73‐fold lower LC50 for UV‐treated NQ compared with NQ parent compound in C. dubia . Moores et al () demonstrated the greatest increase in toxicity yet observed for UV‐degraded NQ, where 90% UV degradation of NQ elicited a 1240‐fold increase in toxicity in Daphnia pulex .…”
Section: Discussionmentioning
confidence: 55%
“…Information on subchronic or chronic toxicity of NQ to fathead minnows was not found in the available literature; therefore, future studies comparing the chronic toxicity of parent MeNQ and NQ including concentrations approaching their limit of solubility in water are warranted to determine if these compounds elicit lethal and sublethal effects in fathead minnows. (Table 3), the magnitude of increased toxicity is lower than has been reported for UVdegraded NQ in previous experiments Kennedy et al 2017;Moores et al 2020b). Kennedy et al (2017) reported a 73-fold lower LC50 for UV-treated NQ compared with NQ parent compound in C. dubia.…”
Section: Subchronic Toxicitymentioning
confidence: 48%
See 1 more Smart Citation
“…37 Overall, DNAN is the most toxic of the IHE constituents. 38 The toxicity of DNAN, and two of its amino derivatives towards nitrifiers, aerobic heterotrophs, methanogens and the bioluminescent bacterium, Aliivibrio fischeri has been investigated. 24 The results indicated that reduction to diaminoanisole (uncommon under aerobic conditions) was required to lower DNAN toxicity.…”
Section: Dnanmentioning
confidence: 99%
“…52 Finally, a study of photolysis of IMX-101 and the individual constituents indicates a 100-times increase in toxicity of NTO to Ceriodaphnia dubia after photolysis, but questions remain about the underlying cause of the toxicity increase. 38…”
Section: Dnanmentioning
confidence: 99%